Design, Development, and Performance Evaluation of a Closed-System Batik Fabric Drying Machine for Small-Scale Industry Applications - Arifia Ekayuliana; Fathan Dewadi; Nabila Yudisha; Ibnu Rosid; Al Fauzi; Muhamad Purdiatama; Adinda Ludwika; Ahmad Royan; Muhammad Nurcholis (Engineering and Technology International Journal, 2025)
This study presents the design and performance evaluation of a closed-system batik fabric drying machine for small-scale industries. The system integrates a spinner for initial dewatering and a hot-air blower with thermostatic control at 60 °C. Experimental tests examined drying time, temperature stability, and fabric quality. Results showed that 2 kg of batik fabric dried in 18 minutes—about 70 % faster than traditional sun drying. The closed-loop air circulation improved thermal uniformity (±1.5 °C deviation) and reduced energy use by 25 %. No color fading or fiber damage occurred, and ultraviolet lamps prevented microbial growth. This design demonstrates that combining mechanical efficiency, thermal control, and ergonomics can enhance energy efficiency and production reliability for micro-scale batik industries.